A new apparatus for investigating gas transport property in geomaterials with ultralow permeability. (3rd July 2023) - Cui, Lin-Yong; Ye, Wei-Min; Ji, Yu-Heng; Xu, Long; Ye, Guan-Lin; Ye, Bin; Chen, Bao; Cui, Yu-Jun; Zhang, Feng
Highlights: A temperature controlled triaxial apparatus was developed for investigating gas transport in geomaterials. A gas flux detection unit including a microprocessor and four flowmeters was designed to measure gas outflow. Eddy current sensors were well located for non-contact measurement of specimen deformation. Verification tests were performed on the developed apparatus using Gaomiaozi (GMZ) bentonite. Abstract: The gas flow in geological materials with ultra-low permeability can vary dramatically, i. e., from almost no measurable quantity of gas before breakthrough to a massive gas flux at breakthrough. It is a great challenge to realize the whole process measurement of gas transport in saturated geomaterials with ultra-low permeability. In this work, a newly designed temperature-controlled triaxial apparatus was developed. In which, a water-to-gas-exchanger was designed for precise injection of gas at a constant pressure or constant injection rate, due to that water is less compressible and much more difficult to leak through the seal of a regulator. Meanwhile, eddy current sensors and displacement transducer with high resolutions were utilized to accurately measure the specimen deformation at different locations in a non-contact way to explore the mechanism of gas entry and breakthrough. In addition, a gas flow detection device that contains four gas flowmeters with different measurement ranges and can automatically switch between these flowmeters was developed to monitor the gas outflow of the whole process. To validate the performance of the developed apparatus, systematic gas injection tests on Gaomiaozi (GMZ) bentonite were conducted, during which the helium gas was injected in a constant rate. Real-time data on inlet gas pressure, gas outflow rate, stress state (both isotropic and axial stresses) and volume deformation (both axially and radially) were monitored. Results show that the developed apparatus could successfully capture the gas entry and the subsequent breakthrough points of the compacted bentonite with ultralow permeability. For compacted bentonite with high saturation, capillary flow, dilatant flow and interfacial leakage could co-exist during the gas transport process and the dominated mechanism was closely related to the gas injection pressure.